Synthesis, optical constants, optical dispersion parameters of CuO nanorods - Yahia, I. S.; Farag, A. A. M.; El-Faify, S.; Yakuphanoğlu, Fahrettin; Al-Ghamdi, Attieh A. (Elsevier Gmbh, 2016)
Thin films of CuO nanorods with 300 nm thickness were prepared by using non-vacuum technique, spin coating sal gel technique. Surface morphology of CuO films were analyzed using atomic force microscopy, AFM. Thin films of CuO have nanorods in its morphology structure. Optical constants, such as refractive (n) and absorption (k) indices of the prepared film were determined using spectrophotometric measurements. Hole mobility of CuO nanorods was deduced at a certain characterized frequency, for the first time for CuO, using the well known Drude equation. Optical transition type was found to be direct allowed with energy of 2.78 eV. From optical constants analysis for CuO films, the real (81) and imaginary (62) dielectric constants, optical conductivity and dissipation factor were also studied. Comparison of the obtained results with the available experimental data for previously published ones are also considered. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Nano-structure CuO thin film; Sol-gel; Optical constants; Optical dispersion parameters; Dielectric properties